ATL. Issue 7 (1st September 2012) - Lerman, Hedva; Bar-On, Shikma; Helpman, Limor; Even-Sapir, Einat; Grisaru, Dan
Abstract : Objective: Positron emission tomography/computed tomography (PET/CT) is an important tool in oncology for assessment of disease extent and recurrence. Recognition of benign fluorodeoxyglucose (FDG) uptake promotes correct interpretation of imaging data. This study assesses the appearance of benign uterine leiomyomas (ULs) on PET/CT and evaluates possible hormonal influences. Patients and Methods: This was a retrospective study performed in a tertiary referral cancer center in Israel. One hundred fifty-two women with nongynecologic malignancies were referred for PET/CT scans, with incidental UL on imaging. Information on menopausal status and menstrual phase and on the use of oral contraceptives, hormone replacement therapy, and selective estrogen receptor modulators (SERM) was collected. Fluorodeoxyglucose uptake measured as standard uptake value (SUV) was obtained for UL, normal myometrium, and gluteus muscle. Changes associated with menopausal status, menstrual cycle phase, and the use of oral contraceptives, hormone replacement therapy, and SERM were assessed. Results: The mean ± SD SUV in UL for the entire cohort was 1.39 ± 0.65 and was higher than in myometrium (1.24 ± 0.33) and gluteus muscle (0.48 ± 0.36). Fluorodeoxyglucose uptake was similar in UL and in myometrium during the preovulatory (1.42 ± 0.31 vs 1.23 ± 0.34) and postovulatory (1.23 ± 0.34 vs1.38 ± 0. 4) periods. During ovulation, SUV was significantly higher in UL (1.62 ± 0.39) than in normal myometrium (1.12 ± 0.15; P = 0.01). Uterine leiomyoma FDG uptake in premenopausal women (1.47 ± 0.32) was higher than in postmenopausal women (1.29 ± 0.41; P < 0.02). The UL/gluteus SUV ratio in patients on hormone replacement therapy (2.53 ± 0.23) was significantly higher than in untreated patients (1.27 ± 0.92; P = 0.05). Lower uptake was recorded in patients on SERM (SUV, 1.1 ± 0.24) than in untreated patients (SUV, 1.41 ± 0.36; P < 0.01). Conclusion: Fluorine 18 FDG uptake in UL may be estrogen dependent. Endogenous estrogen and hormone replacement therapy increase FDG uptake, whereas withdrawal of estrogen by menopause or SERM decreases uptake.